Calculation of irradiance distribution on PV modules by combining sky and sensitivity maps. (1st July 2017) - Santbergen, R.; Muthukumar, V.A.; Valckenborg, R.M.E.; van de Wall, W.J.A.; Smets, A.H.M.; Zeman, M.
Highlights: We present a new model to predict the irradiance on PV modules. It is flexible and can be used for PV modules with shading or reflectors. The model has been validated experimentally. We use it to find the optimum orientation of a PV facade with mirror reflectors. Abstract: Photovoltaic (PV) modules receive both direct light from the sun and scattered light from the sky, ground and nearby objects. The calculation of incident irradiance becomes complex when nearby objects cast shadows or reflect sunlight onto the PV modules. In this paper a flexible irradiance model is presented that takes all these effects into account by combining a so-called sky map, obtained from the Perez model, with a sensitivity map, generated using a ray tracing software. This irradiation model is validated for a PV facade that combines PV modules with mirror reflectors and is shown to be a flexible tool to accurately predict the irradiance distribution.